2013
DOI: 10.9799/ksfan.2013.26.4.850
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Autoclave and Microwave Treatments for Quality of Wet Noodles

Abstract: This study was conducted to determine the effects of physical treatments for quality of wet noodles. Noodles were being tried with a microwave (for 1 min), an autoclave (for 30 or 50 min), and both autoclave and microwave (for 30/1 min or 50/1 min). The results showed that the pH levels were slightly decreased after treatments of autoclave and autoclave/ microwave. The moisture contents were considerably decreased as compared to the control except autoclave (50 min). After all treatments, the lightness was dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The best method for carrot fusilli drying process is 75 0 C for 3 hours. The opposite research [24] used drying method by pressurized heating and microwave; pressurized heating for 50 minutes treatment and microwave treatment for more than 1 minute is confirmed that it is not good. In addition, 30 minutes is in under pressure of heating and microwave in 1 minute was selected.…”
Section: Fig 1 Raw Carrot Fusillimentioning
confidence: 94%
“…The best method for carrot fusilli drying process is 75 0 C for 3 hours. The opposite research [24] used drying method by pressurized heating and microwave; pressurized heating for 50 minutes treatment and microwave treatment for more than 1 minute is confirmed that it is not good. In addition, 30 minutes is in under pressure of heating and microwave in 1 minute was selected.…”
Section: Fig 1 Raw Carrot Fusillimentioning
confidence: 94%